Roving the trail of images: questioning heritage and a tradition of ethnographic writing in Portugal - Medeiros, A. (Revista Anthropológicas, 2016)
Taking the history of ethnographic interests in Portugal as my main frame of reference, I try to relate some present day perceptions of regional heritage and identity to its origins in late XIXth and early XXth century procedures of image making and the diffusion of nationalistic ideology.